2017
DOI: 10.3389/fcvm.2017.00003
|View full text |Cite
|
Sign up to set email alerts
|

A Useful Tool As a Medical Checkup in a General Population—Bioelectrical Impedance Analysis

Abstract: Accumulation of visceral fat leads to metabolic syndrome and increases risks of cerebro-cardiovascular diseases, which should be recognized and improved at the early stage in general population. Accurate measurement of visceral fat area (VFA) is commonly performed by the abdominal cross-sectional image measured by computed tomography scan, which is, however, limited due to the radiation exposure. The bioelectrical impedance analysis (OMRON, HDS-2000 DUALSCANR) has been recently developed to measure VFA, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…In this study, performing dual BIA and CT on the same day increased the robustness of our findings. In previous studies about general population, VFA estimated by impedance analysis correlated with VFA estimated by CT [2630] and also correlated with parameters of obesity such as BMI, waist circumference and waist-hip ratio [31]. Gomez et al and Park et al reported bioimpedance analysis tends to underestimate VFA compared with CT [2730].…”
Section: Discussionmentioning
confidence: 91%
“…In this study, performing dual BIA and CT on the same day increased the robustness of our findings. In previous studies about general population, VFA estimated by impedance analysis correlated with VFA estimated by CT [2630] and also correlated with parameters of obesity such as BMI, waist circumference and waist-hip ratio [31]. Gomez et al and Park et al reported bioimpedance analysis tends to underestimate VFA compared with CT [2730].…”
Section: Discussionmentioning
confidence: 91%
“…However, after fully adjusting for covariates, only the association with waist circumference in both sexes and glucose among women remained significant. Several studies have reported an association between MetS and the phase angle, and MetS has been linked to disturbances of the cell membrane and its surrounding milieu (28,29). One explanation for the difference in our study is that our MetS groups were relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is plausible that these factors would lead to higher C M in those with IR (31‐33). Some conditions that are comorbid to IR, such as those of MetS, may exert similar effects on the membrane (28,29). Therefore, future studies are needed to examine the specific mechanisms by which IR would influence C M and determine the sensitivity and specificity of the association between C M and IR.…”
Section: Discussionmentioning
confidence: 99%
“…The measurements of body site for VFA and SFA were measured at the level of umbilicus with a visceral fat analyzer (DUALSCAN HDS-2000, Omron Healthcare Kyoto, Japan) using the abdominal dual BIA method. 19 , 20 The resultant values were based on the impedance indicated by the difference in electrical conductivity between fat and non-fat tissue. Two paths were used to measure the impedance.…”
Section: Methodsmentioning
confidence: 99%